Synthesis, characterisation and thermo-physical investigations on magnesia nanoparticles dispersed in ethylene glycol–DI water (50:50) - Krishnan Sasidharan, Suseel Jai; KrishnaMurthy, Nagarajan Parasumanna; R., Mamat; Sathyamurthy, R. (The Institution of Engineering and Technology, 2018)
In the present work, magnesia nanoparticles (17 nm) were synthesised by solution combustion and characterised using X-ray diffraction and scanning electron microscopy. Nanofluid prepared by magnesia dispersion in ethylene glycol and deionised water (50:50) is characterised using Fourier transform infrared, dynamic light scattering (DLS) and Zeta potential measurement. The -41 mV zeta potential confirms nanofluid stability. The average particle size in the nanofluid obtained by the DLS method is 33 nm, whereas the crystallite size is 17 nm as per the Scherrer relation. The nanofluid properties were determined under varying volume concentration (0.025, 0.05, 0.1, 0.2%) and temperature (25–60°C). The viscosity measured by using a rotational viscometer decreases with increase in the temperature, whereas the thermal conductivity and specific heat, measured by using a KD2 Pro analyser and a differential scanning calorimeter, respectively, increases. With the increase in volume concentration, thermal conductivity, and viscosity increases, whereas specific heat decreases. The maximum thermal conductivity enhancement and specific heat diminution was 15.6 and 20.5%, respectively, for 0.2% concentration and the minimum viscosity was 2.2% for 0.025% concentration at 60°C. Based on the measured data, new correlations have been proposed.